Limit load analysis of thin-walled as-fabricated pipe bends with low ovality under in-plane moment loading and internal pressure. (November 2019) - Sorour, Sherif S.; Shazly, Mostafa; Megahed, Mohammad M.
Abstract: The fabrication of pipe bends using rotary pipe bending (RPB) process results in geometrical imperfections as described by cross-sectional ovality and wall thickness variations which affect the pipe bends performance during service. Previous studies whether ignores these imperfections (Ideal pipe bend (IB)) or assume these imperfections in their analysis (Assumed shape bend (AS)). The objective of the present work is to investigate, using non-linear finite element analysis, the effect of the residual stresses and the presence of the inherited geometrical imperfections (low ovality) obtained from RPB process of 90° pipe bends on their load carrying capacities as compared with the IB and AS models. RPB process with basic tooling configuration is first simulated to obtain the as-fabricated 90° pipe bend. The results of this step were verified against published experimental results and analytical solutions, and compensated for springback. The pipe bend was then subjected to different combinations of loads (in-plane moment and internal pressure) to construct a comparative limit load diagram. Within the scope of our study, results have shown that the presence of the residual stresses remarkably reduces the pipe bend load-carrying capacity. IB model results in non-conservative results as geometrical imperfections lower the load carrying capacity of the pipe bend, while the AS model has been found to be invalid for cases where a mandrel is used in RPB process. Highlights: Limit loads for as-fabricated, annealed, ideal, and idealized pipe bends are compared. Geometrical imperfections lower the limit loads of the As-Fabricated pipe bend with low ovality. Ideal pipe bend model provides non-conservative results for limit loads. High residual stresses in pipe bends made with mandrels limit their load carrying capacity.